INFORMATION SYSTEM DESIGN OF PERFORMANCE ACHIEVEMENTS MONITORING IN THE UNIVERSITY: A CASE STUDY IN BINUS UNIVERSITY - Ibrahim, Irma Irawati; Tho, Cuk (CommIT (Communication and Information Technology) Journal, 2012)
Dashboard is a computer interface that displays a variety of charts, graphs, tables, which are selected reports from various data that are considered important to display rapidly, with an attractive appearance, dynamic, and relevant so that it can immediately be seen quickly to analyze a condition. Dashboard information system is widely used in various companies as a support system for decision-making where Dashboard usually displays data business trends of the company or the achievement of KPI (Key Performance Indicator) of a company. The method used is descriptive analysis by means of collecting information that areimportant for universities to be considered asthe Key Success Factors (KSF) of the university, and then, the design of the dashboard is made in accordance with these important factors.The result of this study is a grand design of information systems for the university performance monitoring, starting from the reception of students, faculty performance, student academic achievement, effectiveness and efficiency of services, including graduates. It is expected that by the time the system has been fully implemented, the university can take action quickly and accurately with respect to the required conditions.Keywords: Information System Dashboard; Dashboard; Academic Dashboard; University Dashboard